Cosec square theta + sec square theta = tan square theta + cot square theta
Answers
Answered by
1
Answer:
Step-by-step explanation
LHS=cosec square theta+sec square theta
=1/sin square theta+1/cos square theta
=cos square theta +sin square theta /sin square theta. Cos sqare theta
=cos square theta /sin square theta +sin square theta /cos square theta
=cot square theta +tan square theta
=tan square theta +cot square theta =RHS
LHS=RHS
Cosec square theta +sec square theta =tan square theta +cot square theta is proved.
Similar questions
Computer Science,
7 months ago
English,
7 months ago
Biology,
1 year ago
Social Sciences,
1 year ago
Math,
1 year ago
Physics,
1 year ago